2011
DOI: 10.1186/1754-6834-4-55
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and enzymatic digestibility of sugarcane clones selected for varied lignin content

Abstract: BackgroundThe recalcitrance of lignocellulosic materials is a major limitation for their conversion into fermentable sugars. Lignin depletion in new cultivars or transgenic plants has been identified as a way to diminish this recalcitrance. In this study, we assessed the success of a sugarcane breeding program in selecting sugarcane plants with low lignin content, and report the chemical composition and agronomic characteristics of eleven experimental hybrids and two reference samples. The enzymatic digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
2
43

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 35 publications
9
100
2
43
Order By: Relevance
“…The values for lignin content presented in our study are significantly lower than those previously reported for sugarcane bagasse (Lopes et al, 2011;Masarin et al, 2011;Rezende et al, 2011). Sugarcane bagasse is the residue produced after Suc extraction and is composed of 39% cellulose, 25% hemicelluloses, and 23% lignin, among other minor components (Carroll and Somerville, 2009).…”
Section: Discussioncontrasting
confidence: 52%
“…The values for lignin content presented in our study are significantly lower than those previously reported for sugarcane bagasse (Lopes et al, 2011;Masarin et al, 2011;Rezende et al, 2011). Sugarcane bagasse is the residue produced after Suc extraction and is composed of 39% cellulose, 25% hemicelluloses, and 23% lignin, among other minor components (Carroll and Somerville, 2009).…”
Section: Discussioncontrasting
confidence: 52%
“…O bagaço in natura foi também caracterizado com realção à quantidade de extrativos, conforme descrito por Masarin et al (2011).…”
Section: Métodos Analíticosunclassified
“…Pretreatment can break down lignin and hemicellulose bonds, disrupt the crystalline arrangement of cellulose, increase digestibility and cell wall porosity, and improve accessibility to enzymes during hydrolysis [24].…”
Section: Deconstruction Of Lignocellulosic Biomass and Its Usesmentioning
confidence: 99%